Perception Of Artificial Intelligence Adoption on Audit Quality - Herfanda Nugraha, Georgius Chandra (ABIS: Accounting and Business Information Systems Journal, 2024)
This study investigates the adoption of Artificial Intelligence (AI) in auditing. The study aimed to identify the effects of AI adoption on audit quality and whether the technology readiness dimension moderated the relationship. The data were collected via surveys and analyzed by using multiple regression. The results showed that optimism affected AI adoption, while insecurity did not. Interesting results found that innovation and discomfort did not moderate the relationship in the model. This research has implications for companies and educational institutions concerned with future accounting profession training on new technology skills and competencies, especially AI and planning technology adoption strategies to improve audit quality. This research provides initial insight into the psychological factors influencing AI adoption in auditing and leads to further research with pre-adoption and post-adoption identification.